Proceedings of 22nd International Workshop on Vertex Detectors — PoS(Vertex2013) 2014
DOI: 10.22323/1.198.0027
|View full text |Cite
|
Sign up to set email alerts
|

Planar sensors for future Vertex and Tracking Detectors

Abstract: With increasing instantaneous and integrated luminosities of collision experiments the requirements on position sensitive detectors and sensor materials increase rapidly. Numerous R&D projects of several collaborations have investigated known and new materials with respect to their range of application. This report gives an overview of the current activities and common understanding of planar sensors concentrating on operational aspects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…A comprehensive program has been carried out to identify suitable silicon materials [3]. Measurements on the charge collection of 300 µm thick silicon confirmed earlier studies [4] that strip sensors with collection of holes for signal generation have greater degradation than sensors with collection of electrons for signal generation (Fig.8).…”
Section: Radiation Tolerant Sensorssupporting
confidence: 62%
See 1 more Smart Citation
“…A comprehensive program has been carried out to identify suitable silicon materials [3]. Measurements on the charge collection of 300 µm thick silicon confirmed earlier studies [4] that strip sensors with collection of holes for signal generation have greater degradation than sensors with collection of electrons for signal generation (Fig.8).…”
Section: Radiation Tolerant Sensorssupporting
confidence: 62%
“…Measurements on the charge collection of 300 µm thick silicon confirmed earlier studies [4] that strip sensors with collection of holes for signal generation have greater degradation than sensors with collection of electrons for signal generation (Fig.8). In addition, irradiated sensors with n-type bulk have shown non-Gaussian noise, resulting in an irreducible rate of fake hits [3]. This phenomenon, also called Random Ghost Hits (RGH), was also observed on p-type sensors with a too high p-stop concentration [5].…”
Section: Radiation Tolerant Sensorsmentioning
confidence: 98%
“…The CMS tracker will be replaced completely. The new tracker will be equipped with n-in-p type sensors as several R&D studies showed an enhanced radiation hardness of this sensor type [1,2,3]. The expected fluence in CMS of the inner layers (R∼20 cm) equipped with silicon strip sensors is about F = 1 × 10 15 n eq cm −2 .…”
Section: Lhc and Cms Upgradementioning
confidence: 99%
“…Signal measurements have been performed with the ALiBaVa 3 System based on the analogue Beetle chip used in the LHCb experiment. Penetrating electrons from the β − decay of a Sr 90 3 source have been triggered by a scintillator and measurements have been performed before and after mixed irradiation up to F = 1.5 × 10 15 n eq cm −2 (R = 20 cm). From the batch of samples#3, where two different p-stop distances (16 µm and 25 µm) have been produced, no difference in charge collection in dependence on the p-stop distance to n+ strips has been observed.…”
Section: Defectmentioning
confidence: 99%
“…Surface resistivity and p-stop concentration, pstop width and geometry adjust the current. 200 µm thickness of the active volume was selected and n-in-p technology was chosen as a result of previous studies [5]. …”
Section: Ps Module For the Cms Phase 2 Upgradementioning
confidence: 99%